Workplace optimisation - Lim, Kenn Zheng Jie (Nanyang Technological University, 2023)
Business Intelligence and Analytic tools possess the ability to transform a business and improve its operations significantly. With this field of analytics gaining traction in today’s fast paced business environment, a wide array of tools are now available, and have been adopted to tackle a variety of problems for numerous business applications. Adoption of such tools are vital for businesses to maintain their competitive edge in their industries, as well as to optimize business operations for increased efficiency and productivity. However, with a vast array of tools available, purpose and limitations are crucial in helping businesses determine the appropriate tools to deploy. This paper discusses how Evoqua Water Technologies, an industrial leader in providing water and wastewater treatment solutions, will be able to utilize such tools to optimize their business efficiency.